Enhanced nonlinear optical properties of reduced graphene oxide modified by Mn-doped semiconductor CdS nanoparticles as photonic materials. (25th August 2022) - Yuan, Xue; Wang, Fangfang; Liang, Yuning; Zhu, Baohua; Gu, Yuzong
Abstract: Graphene has broad prospects for application in photonic devices. However, its zero-band gap limits its nonlinear optical (NLO) properties, and thus, its application. In this study, we synthesized reduced graphene oxide modified by Mn-doped semiconductor CdS nanoparticles (RGO/CdS:Mn) via a solvothermal method to study the development of NLO properties of graphene. The structures, morphologies and basic physical properties of RGO, CdS, RGO/CdS, and RGO/CdS:Mn were characterized. The third-order optical nonlinearities were tested by the Z-scan technique using a mode-locked Nd:YAG laser operating at 532 nm with a 30 ps pulse width. The results showed that the nonlinear susceptibility and saturation absorption of RGO/CdS:Mn were 15.3 and 26 times higher than those of RGO, respectively. The mechanism of the enhancement was analyzed based on the charge transfer between and within the components, and Mn doping produced trapping effect. The significantly improved optical nonlinearity of RGO/CdS:Mn lays a foundation for its applications in photonic devices.